Mobile Application for Army Polytechnic Smart Card Transactions Using NFC and QR Code: Telekomunikasi Militer - Aria Sonta; Theresia Dwi Siwi Candra Widiyati; Muhammad Ridwan (Jurnal Telkommil, 2026)
QR Code Scanning-Based Mobile Membership Checker Application